2018
DOI: 10.1007/s00253-018-9372-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced synthesis of poly gamma glutamic acid by increasing the intracellular reactive oxygen species in the Bacillus licheniformis Δ1-pyrroline-5-carboxylate dehydrogenase gene ycgN-deficient strain

Abstract: Poly gamma glutamic acid (γ-PGA) is an anionic polyamide with numerous applications. Previous studies revealed that L-proline metabolism is implicated in a wide range of cellular processes by increasing intercellular reactive oxygen species (ROS) generation. However, the relationship between L-proline metabolism and γ-PGA synthesis has not yet been analyzed. In this study, our results confirmed that deletion of Δ1-pyrroline-5-carboxylate dehydrogenase gene ycgN in Bacillus licheniformis WX-02 increased γ-PGA y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…revealed that the overexpression of the gene ycgM (encoding proline dehydrogenase) and ycgN (encoding Δ 1 -pyrroline-5-carboxylate dehydrogenase) decreases the production of γ-PGA by B. licheniformis WX-02 by disturbing the intrinsic reactive oxygen species level . In contrast to B.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…revealed that the overexpression of the gene ycgM (encoding proline dehydrogenase) and ycgN (encoding Δ 1 -pyrroline-5-carboxylate dehydrogenase) decreases the production of γ-PGA by B. licheniformis WX-02 by disturbing the intrinsic reactive oxygen species level . In contrast to B.…”
Section: Resultsmentioning
confidence: 99%
“…Real-time reverse transcription (qRT-PCR) was applied to confirm the RNA-Seq results. The procedure of qRT-PCR was performed as described before . The specific primers used for qRT-PCR are presented in Table S2.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Proline metabolism is of vital importance for bacterial growth. Li et al [11] reported that the lag phase of deletion of the ycgN gene (the gene for P5CDH in B. licheniformis) in B. licheniformis was prolonged by 4-8 h compared to the WT. Accordingly, a similar situation was also observed in S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…PRODH and P5CDH are the two enzymes in this reaction, but P5CDH could affect electron transfer and the TCA cycle. Importantly, Halsey [10] and Li et al [11] reported that P5CDH-deficient strains of MRSA had significant growth yield defects whereas PRODH-deficient strains did not. Therefore, P5CDH was speculated to be a target of celastrol (Figure 4D).…”
Section: Discovery Of a Novel Anti-mrsa Target From Multi-omics Analysismentioning
confidence: 99%
See 1 more Smart Citation